2007
DOI: 10.1089/sur.2006.013
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Efficacy of Coated Vicryl Plus® Antibacterial Suture in an Animal Model of Orthopedic Surgery

Abstract: Under simulated conditions of severe intraoperative contamination, the antibacterial suture reduced the number of positive cultures after surgery by 66.6%. Judging from the available clinical information, its use might contribute to reducing the number of infected implants by 25.8%. Human studies are needed to determine the clinical implications of these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 13 publications
0
43
0
1
Order By: Relevance
“…Wound closure with triclosan-impregnated sutures resulted in 66.6% reduction in positive culture from tissue adjacent to the steel implant, thereby showing that the antibacterial influence extends to the surrounding tissue. 40 In addition, these sutures may have an immunomodulatory effect that is favorable to tissue healing as the healing factors such as hydroxyproline and transforming growth factor-β and inflammatory mediators such as tumor necrosis factor-α in contaminated wounds closed with triclosan-impregnated sutures approached that of clean wounds. 37 Previous studies by Justinger et al 41 and Fleck et al 42 have demonstrated statistically significant reductions in wound infection rates in laparotomy and sternal wounds, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Wound closure with triclosan-impregnated sutures resulted in 66.6% reduction in positive culture from tissue adjacent to the steel implant, thereby showing that the antibacterial influence extends to the surrounding tissue. 40 In addition, these sutures may have an immunomodulatory effect that is favorable to tissue healing as the healing factors such as hydroxyproline and transforming growth factor-β and inflammatory mediators such as tumor necrosis factor-α in contaminated wounds closed with triclosan-impregnated sutures approached that of clean wounds. 37 Previous studies by Justinger et al 41 and Fleck et al 42 have demonstrated statistically significant reductions in wound infection rates in laparotomy and sternal wounds, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…15 Triclosan coating has shown effectiveness in vitro against strains of Staphylococcus aureus, Staphylococcus epidermidis, MRSA, methicillin-resistant Staphylococcus epidermidis (MRSE), vancomycin-resistant Enterococcus faecalis, Pseudomonas aeruginosa, and Escherichia coli 16,17 and has proven beneficial in animal models (rat and guinea pig). 7,[18][19][20] Recently, a new suture material has emerged on the market that is characterized by barbs projecting from a monofilament base. To our knowledge, three different barbed sutures are currently on the market: Quill TM (Surgical Specialties Corporation), V-loc TM (Covidien), and Stratafix TM (Ethicon).…”
mentioning
confidence: 99%
“…47 In a clinical prosthetic study, which evaluated the incidence of CSF shunt infections following use of triclosan-coated or conventional sutures, the infection rate was significantly reduced in the triclosan-coated suture group (4.3% vs 21%). 48 A clinical study compared triclosan-coated suture with standard PDS after more than 2000 mid-line laparotomies and found that the antimicrobial-coated suture significantly decreased the number of SSIs (4.9% vs 10.8%).…”
Section: Antimicrobial Sutures: What Are the Benefits?mentioning
confidence: 99%